2011
DOI: 10.3354/esr00337
|View full text |Cite
|
Sign up to set email alerts
|

Global phylogeography of the dusky shark Carcharhinus obscurus: implications for fisheries management and monitoring the shark fin trade

Abstract: Genetic stock structure information is needed to delineate management units and monitor trade in sharks, many of which are heavily exploited and declining. The dusky shark Carcharhinus obscurus is a large apex predator that is sought after for its fins and is considered highly susceptible to overexploitation. The International Union for the Conservation of Nature (IUCN) classifies this species as 'Vulnerable' globally and 'Endangered' in the northwest Atlantic. We make the first assessment of global stock stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 34 publications
(23 reference statements)
2
29
2
Order By: Relevance
“…C. obscurus attains a large size (Last & Stevens 2009) and is suspected of undergoing long-range temperature-driven migrations on a seasonal basis, with tagging studies revealing an ability to travel considerable distances (Hussey et al 2009, Rogers et al 2013. Our findings of genetic subdivision between eastern and western Australia, however, challenge those of Ovenden et al (2009) and also Benavides et al (2011b), who failed to detect genetic differentiation between these same 2 locations using control region sequence data. We also provide evidence for and against the findings of Ovenden et al (2009) relating to genetic subdivision between Australia and Indonesia.…”
Section: Regional Gene Flow In Carcharhinus Obscuruscontrasting
confidence: 56%
See 2 more Smart Citations
“…C. obscurus attains a large size (Last & Stevens 2009) and is suspected of undergoing long-range temperature-driven migrations on a seasonal basis, with tagging studies revealing an ability to travel considerable distances (Hussey et al 2009, Rogers et al 2013. Our findings of genetic subdivision between eastern and western Australia, however, challenge those of Ovenden et al (2009) and also Benavides et al (2011b), who failed to detect genetic differentiation between these same 2 locations using control region sequence data. We also provide evidence for and against the findings of Ovenden et al (2009) relating to genetic subdivision between Australia and Indonesia.…”
Section: Regional Gene Flow In Carcharhinus Obscuruscontrasting
confidence: 56%
“…Portnoy et al (2010) observed genetic subdivision between eastern and western Australia in C. plumbeus based on mitochondrial DNA (mtDNA), while Ovenden et al (2009) and Benavides et al (2011b) reported evidence for genetic homogeneity between the same 2 regions in C. obscurus. Ovenden et al (2009) also raised the possibility of limited dispersal across the Timor Trench in the latter species through a finding of genetic differentiation between western Australia and central Indonesia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the size range of the species was represented in all time periods, and geographic variation in parameters due to genetic effects is likely to be minimal; all samples used in this study were likely obtained from the same population of dusky sharks (Benavides et al 2011). Thus, while we acknowledge that there are limitations to these analyses in terms of sample sizes and frequency distributions, we also feel it would have been remiss not to test for density-dependant differences due to the exploitation history of this species.…”
Section: Discussionmentioning
confidence: 99%
“…The dusky shark is a common coastal pelagic carcharhinid that is widely distributed in the world's oceans (Compagno 1984) and considered a single, genetic stock in the northwest Atlantic and GOM (Benavides et al 2011). It is considered one of the most vulnerable species to overexploitation due to its combination of slow growth, late age at maturity (19-21 years), small litter sizes (3-12 embryos), and tri-annual gestation (Natanson et al 1995;Romine et al 2009).…”
Section: Introductionmentioning
confidence: 99%